101k views
1 vote
Which expression is equal to (f + g)(x)?

Which expression is equal to (f + g)(x)?-example-1
User Venca
by
5.6k points

2 Answers

4 votes

Answer:

B.

Explanation:


= f(x) + g(x)\\= \sqrt{x^(2) +28x+196} +x^(3) -729\\factor (x^(2) +28x+196) to ((x+14)^(2))\\= \sqrt{(x+14)^(2) } +x^(3) -729\\= x+14+x^(3) -729\\=x^(3) +x-715

User Diegopau
by
4.9k points
4 votes

ANSWER

B.


(f + g)(x) = {x}^(3) + x- 715

EXPLANATION

The given functions are:


f(x) = \sqrt{ {x}^(2) + 28x + 196}

This is the same as


f(x) = \sqrt{ {(x + 14)}^(2) }


f(x) = x + 14

and


g(x) = {x}^(3) - 729


(f + g)(x) = f(x) + g(x)


(f + g)(x) = x + 14 + {x}^(3) - 729


(f + g)(x) = {x}^(3) + x- 715

The correct answer is B

User Vasilov Artur
by
5.4k points